2016
DOI: 10.1002/nau.23119
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow‐up study of artificial urinary sphincter placement preserving the bulbospongiosus muscle

Abstract: Our study suggests that placement of AUS preserving the bulbospongiosus muscle is technically easy and efficient, reports excellent continence rates and lower urethral erosion rates, and could delay the onset of urethral atrophy compared to other surgical procedures used for sphincter placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
10
0
6
Order By: Relevance
“…A further potential bias of our study is that the cuff placement technique was not analyzed. A bulbospongiosus-sparing technique to reduce atrophy [6] was not performed in our participating centers. Transcorporal cuff placement was, however, applied in patients with small urethral circumferences, though precise analysis was not possible due to inconsistent/missing data.…”
Section: Discussionmentioning
confidence: 99%
“…A further potential bias of our study is that the cuff placement technique was not analyzed. A bulbospongiosus-sparing technique to reduce atrophy [6] was not performed in our participating centers. Transcorporal cuff placement was, however, applied in patients with small urethral circumferences, though precise analysis was not possible due to inconsistent/missing data.…”
Section: Discussionmentioning
confidence: 99%
“…This involved a similar initial dissection, but was associated with increased revision rates, probably due to muscle atrophy under the cuff. More recently, Collado Serra et al reported their results using a bulbospongiosus muscle‐preserving technique, which included dorsal urethral dissection similar to our present technique. They reported their results on 82 patients over an 11‐year period, reporting a 77% dry rate at 1 year and, notably, only one erosion during the that time.…”
Section: Discussionmentioning
confidence: 66%
“…Serra et al [37], in 2016, described a bulbospongiosus-muscle-sparing AUS implantation technique, with the idea that muscle preservation may decrease the risk of urethral injury during the dissection and may also better preserve the flow of blood to the urethra, thus preventing both long-and short-term complications. In this series of 82 consecutive patients, Serra et al reported an AUS survival rate, defined as the loss of continence or mechanical failure during follow-up, of 95.5% (95%CI: 89.4-100%) at 24 mos and 62.6% (95%CI: 45.5-79.6%) at 60 mos, similar to our findings, while somewhat better functional outcomes were reported (dry rate of 76.8% and social continence rate of 92%).…”
Section: Discussionmentioning
confidence: 99%